Enhancing rural development in Mberengwa North through community radio. case of YA FM - Gumbo, Munyaradzi (2017)
This study examines the role of YA FM in enhancing rural development in Mberengwa North district. The research sought to identify and review the major contributions that were brought by YA FM in the development of rural communities. The main focus of this research was to identify programmes related to rural development and how these are stimulating development in rural areas. Despite some challenges and personal agendas, YA FM has managed to design programmes that have positively influenced the livelihoods of the marginalised people in Mberengwa district. These programmes cover areas such as political, business, health, edutainment, agriculture, legal and social issues among others. Most of these programmes feature experts and professionals who are well-versed with topics under discussion on a particular day. These programmes address matters of interest to the community thus participation of audience is among the methods being used to enhance development. Listeners can participate through phone-ins, text messages and social media platforms (WhatsApp, Twitter and FaceBook). A qualitative research paradigm was used for the study where focus groups, in-depth interviews and direct observation were used to gather data and content analysis was used to analyse data. The interpretation of the data gathered was anchored on development and media theories propounded by various international scholars.